The Development of Short Film Indigenous Counseling Kontemplasi Nyawang Karep - Budi Sarwono; Yohanes Heri Widodo; Antonius Ian Bayu Setiawan (Bisma The Journal of Counseling, 2025)
Ideally, counseling should be grounded in approaches that align with the client’s cultural background and lived experiences so that the therapeutic process can become more authentic and meaningful. However, counseling practices are still dominated by Western models that pay insufficient attention to local wisdom, creating a gap between theoretical frameworks and practical needs in the field. This study aims to analyze, develop, and validate a counseling learning medium in the form of a short film that presents the concept of Kontemplasi Nyawang Karep from the teachings of Ki Ageng Suryomentaram as a means to strengthen indigenous counseling competencies among students. The research employs the Borg and Gall Research and Development (R&D) model. Data were obtained through validation by media experts and content experts using feasibility assessment instruments, followed by quantitative descriptive analysis. The resulting product consists of nine curated and evaluated scenes of a short film. The findings indicate that the indigenous counseling short film is considered highly feasible by both expert validators. These results highlight the strong potential of short film media as a form of observational learning that helps viewers understand and concretely observe the application of indigenous concepts in counseling practice. This media provides important implications and contributes to the strengthening and development of culturally grounded counseling models.